Evolución y nuevas tendencias en los trabajos sobre didáctica de las ciencias experimentales. Revisión del año 1984 - Mata, A.; Anta, C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2007)
Trends in teaching innovation are presented, according to a bibliometric analy,sis of Spanish bibliography in 1984 about new teaching methods in experimental sciences. Occurrence points, teaching levels and topics in which innovations and new methods are being carried are shown.